CMOS Cascade Sigma-Delta Modulators for Sensors and Telecom Error Analysis and Practical Design - Río Fernández, Rocío; Medeiro Hidalgo, Fernando; Pérez Verdú, Belén; Rosa Utrera, José Manuel; Rodríguez-Vázquez, Ángel (Analog Circuits and Signal Processing, 2006)
CMOS Cascade Sigma-Delta Modulators for Sensors and Telecom: Error Analysis and Practical Design starts with a tutorial presentation of the fundamentals of low-pass sigma-delta modulators, their applications, and their most common architectures. It then presents an exhaustive analysis of SC circuit errors with a twofold outcome. On the one hand, compact expressions are derived to support design plans and quick top-down design. On the other, detailed behavioral models are presented to support accurate verification. This set of models allows the designer to determine the required specifications for the different modulator building blocks and form the basis of a systematic design approach. The book is completed in subsequent chapters with the detailed presentation of three high-performance modulator ICs: the first two are intended for DSL-like applications, whereas the third one is intended for automotive sensors. CMOS Cascade Sigma-Delta Modulators for Sensors and Telecom: Error Analysis and Practical Design contains highly valuable information that is structured to give the reader the necessary insight on how to design SC sigma-delta modulators.